1973
DOI: 10.1152/ajplegacy.1973.225.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemia on function and metabolism of the isolated working rat heart

Abstract: Effects of ischemia on function and metabolism of the isolated wcrking rut heart. Am. J. Physiol. 225(3): 651-658. 1973.-Two techniques have been developed for inducing whole-heart ischemia in the isulated working rat heart, These procedures allowed total coronary Aow to be reduced in hearts that were performing external mechanical work. Reducing the rate of coronary flow resulted in myocardial ischemia as indicated by reduced oxygen delivery and consumption, increased production, and tissue accumulation of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
2

Year Published

1975
1975
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(106 citation statements)
references
References 17 publications
3
100
0
2
Order By: Relevance
“…Similarly, ischemia induced GLUT4 translocation in isolated cardiac myocytes (31). On the other hand, three decades ago Finck et al (32) had shown an ischemia-induced reduction of glucose uptake, a finding that was supported by a recent study that found no increase in glucose uptake despite AMPK activation in ischemic isolated working hearts (33). Similarly, the data regarding ACC are not entirely consistent.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, ischemia induced GLUT4 translocation in isolated cardiac myocytes (31). On the other hand, three decades ago Finck et al (32) had shown an ischemia-induced reduction of glucose uptake, a finding that was supported by a recent study that found no increase in glucose uptake despite AMPK activation in ischemic isolated working hearts (33). Similarly, the data regarding ACC are not entirely consistent.…”
Section: Discussionmentioning
confidence: 86%
“…Alterations in mechanical and metabolic functions of myocardial cells are generally reversible up to 20 minutes following restriction of coronary blood flow, but irreversible damage and cell death occur between 20 and 60 minutes (2)(3)(4)(5)(6)(7). The time of onset of cell death may be directly proportional to the restriction in coronary blood flow.…”
mentioning
confidence: 99%
“…Perfüze edilen sıvı kanüle edilen sol atriyumdan kalbe girer, sol ventrikülden geçerek aorttan çıkar. 78 …”
Section: çAlışan Kalp Modeliunclassified